Melting of Hummock Ice (Staivanie l'da v Torosakh) - Nazintsev,Yu. L. (1973)
The summer thawing of sea ice is one of the main elements in ice forecasting. The polar stations in the Arctic have accumulated extensive data on the thawing and disintegration of ice. However, almost all of the data is related to the smooth surface of an ice cover rather than to hummocks. At the same time, the hummocking zones occupy such an appreciable area that in the continuous and concentrated ice formations, they comprise the main obstacle to the movement of vessels. In this connection, an estimation of the thawing and weakening of ice in the hummocks is of practical interest. Results obtained from measurements in the ice accumulations in the many years' field work of the North-Pole-13 station in 1966 are listed. A simple system for calculating the ice mass destroyed by thawing in the hummocks is suggested. (Author) Draft trans. of Arkticheskii i Antarkticheskii Nauchno-Issledovatelskii Institut. Trudy (USSR) v300 p92-100 1971.